Business model generation . a handbook for visionaries, game changers, and challengers . - Osterwalder, Alexander; Pigneur, Yves.; Clark, Tim, 1956- (Hoboken, NJ : Wiley, 2010)
Offers tools and techniques to systematically understand, design, and implement new business models and renovate and rework old models.
1: Canvas -- Definition of a business model -- The 9 building blocks -- The business model canvas -- 2: Patterns -- Unbundling business models -- The long tail -- Multi-sided platforms -- FREE as a business model -- Open business models -- 3: Design -- Customer insights -- Ideation -- Visual thinking -- Prototyping -- Storytelling -- Scenarios -- 4: Strategy -- Business model environment -- Evaluating business models -- Business model perspective on blue ocean strategy -- Managing multiple business models -- 5: Process -- Business model design process.
Paper Cover.
Includes bibliographical references.
Keywords: Osterwalder, Alexander; Business planning; New business enterprises; Strategic planning; Business planning; New business enterprises; Strategic planning; Innovationsmanagement